Sosialisasi Stop Tindakan Bullying dan Kekerasan Seksual di Sekolah SMAN X Kecamatan Y - Hendra Lukito; Mohamad Ikrom Arasid (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Education plays a fundamental role in shaping character, developing personality, and exploring students' potential. Schools should ideally be safe, comfortable, and conducive spaces for student growth and development. However, reality shows that the school environment is still vulnerable to negative behaviors such as bullying and sexual violence. Bullying is understood as aggressive behavior carried out repeatedly with the aim of harming the victim, whether through physical, verbal, social, or online media (cyberbullying). Meanwhile, sexual violence includes various forms of sexual acts without the victim's consent, which have serious impacts on psychological, social, and academic achievement. Sexual violence in schools not only harms the victims physically but also leaves deep psychological scars that may affect their future. To respond to this problem, KKM Group 30 Bina Bangsa University conducted a socialization activity entitled